2004
DOI: 10.1007/s00464-004-8932-8
|View full text |Cite
|
Sign up to set email alerts
|

Objective analysis of gastroesophageal reflux after laparoscopic heller myotomy: An anti-reflux procedure is required

Abstract: Objective analysis reveals an unacceptable rate of gastroesophageal reflux in laparoscopic Heller myotomy without an antireflux procedure. We therefore recommend performing a concurrent antireflux procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 28 publications
(35 reference statements)
2
22
0
1
Order By: Relevance
“…In particular, heartburn may be confused with regurgitation or substernal pain, while presence of excessive acid in the esophageal lumen may not produce heartburn at all, due to decreased mechanosensitivity and chemosensitivity caused by achalasia [20]. In general, GER symptoms seem not to be related to increased esophageal acid exposure [21][22][23]. Gholoum et al [9] have shown that moderate or severe heartburn after myotomy and fundoplication is associated with a pathologic esophageal acid exposure in at least half of the patients, while a significant proportion of patients, ranging between 7 and 23 percent, may have ''silent reflux'', namely absence of heartburn but increased esophageal acid exposure.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, heartburn may be confused with regurgitation or substernal pain, while presence of excessive acid in the esophageal lumen may not produce heartburn at all, due to decreased mechanosensitivity and chemosensitivity caused by achalasia [20]. In general, GER symptoms seem not to be related to increased esophageal acid exposure [21][22][23]. Gholoum et al [9] have shown that moderate or severe heartburn after myotomy and fundoplication is associated with a pathologic esophageal acid exposure in at least half of the patients, while a significant proportion of patients, ranging between 7 and 23 percent, may have ''silent reflux'', namely absence of heartburn but increased esophageal acid exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Of the 20 patients with some heartburn after surgery, 13 patients rated their heartburn as mild, six as ''moderate,'' and one as ''severe.'' Patients reporting moderate or severe postop heartburn had a GERD-HRQL of 10.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) compared to 1 (0-3.5) for those with no or mild heartburn (p = 0.004). Heartburn score correlated well with GERD-HRQL score (SpearmanÕs rho = 0.79, p = 0.000).…”
Section: Subjective Outcomesmentioning
confidence: 94%
“…In a study of 50 patients with achalasia who underwent laparoscopic Heller myotomy without anti-reflux procedures, significant heartburn was reported in 30% of cases. Twenty fourhour pH monitoring revealed abnormal findings in 11 out of 22 patients tested [53] . However, use of a fundoplication procedure with laparoscopic myotomy reduced the rate of gastro-esophageal reflux (8.8% with a fundoplication vs 31.5% without a fundoplication, P = 0.003) [37] .…”
Section: Surgical Myotomymentioning
confidence: 95%